Antidiabetic Activity of Okra Fruit (Abelmoschus esculentus (L) Moench) Extract and Fractions in Two Conditions of Diabetic Rats - Herowati, Rina (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
Okra (Abelmoschus esculentus (L) Moench) fruit is empirically used in type 2 diabetes mellitus treatment. This research aims to know the antihyperglycemic activity of okra fruit extract and fractions in streptozotocin-nicotinamide (STZ-NA) induced as well as in insulin resistance diabetic rats, the effect on pancreatic cells regeneration, and the effect on immunohistochemical expression of glucose transporter-4. This study used a group of 35 male Wistar rats for STZ-NA induced diabetic model and another group of 35 rats for insulin resistance diabetic model. Gliclazide (0.72mg/kg BW) and metformin (45mg/kg BW) were used as drug control in STZ-NA induced and insulin resistance diabetes, respectively. Okra fruit ethanol extract, n-hexane, ethyl acetate, and water fraction were orally administered with dose of 200; 107; 6 and 86mg/kg BW, respectively, for 28 days after diabetic condition was obtained. Blood glucose level was measured every week. Hematoxylin-eosin staining was used to evaluate the pancreatic cells regeneration, while immunohistochemistry was used to evaluate the expression of glucose transporter-4 in muscle membrane cells, at the end of the treatment. The results revealed that ethyl acetate fraction was the most effective in lowering blood glucose level in both condition of diabetes. Ethyl acetate fraction decreased the necrosis of pancreatic cells in STZ-NA induced diabetic rats and increased the expression of glucose transporter-4 in muscle cell of insulin resistance diabetic rats.